Comparing the Radiation Adaptation in Rat after Receive Lethal Dose of Toxic Permethrin Feeding - Farshid Gheisari (Journal of Global Pharma Technology, 2017)
Human exposure to ionizing radiation has long considered harmful to biological tissue and in sufficient amounts and intensities can be irreversible tissue damage, cancer and even death of an organism cause. On the other hand many researches that have taken place in recent decades show that low doses of ionizing radiation cannot be extrapolated effects (Extrapolation) the results of the effects of high doses predicted. Several cases of the positive effects of low doses of ionizing radiation in the form of bio-cognitive Hormetic or irritant effects have been reported. In this study 60 male Wistar rats with a genetic structure identical all homogenous inbred were randomly divided into 4 groups (3 groups for each of radioisotopes and underlying soil with a high dose control group), divided are. In order to prevent any Bias in the study, Permethrin is fed to all groups with a amount of poison. Mice were coded and only after completion of the test will be Decoding. The highest survival duration pertains to the group that received technetium-99m. Next is Ramsar soil group which is statistically indicative of a significant difference in respect to technetium-99m group. Iodine 131 takes the third rank and it is statistically not indicative of a significant difference with neither of the control and other groups. Low dosages of technetium featuring higher than normal natural radioactivity in Ramsar was selected as challenging dose and orally-fed Permethrin chemical compound was selected as the lethal factor. Data analysis reflects the creation of an adaptive effect subsequent to the prescription of low dosage technetium as well as a synergistic effect exerted by technetium and the regional soil characterized by a high background dosage on test rats’ survival time following to the administration of permethrin lethal dosage.